Temperature-induced germination pulses above the alpine tree line - Audrey Palosse; Alma Piermattei; Jan Esper; Frederick Reinig; Anne Verstege; Max Torbenson; Mirek Trnka; Tito Arosio; Ulf Büntgen (Arctic, Antarctic, and Alpine Research)
Subject to a long research tradition, the tree line is considered an important biogeographic indicator of climate changes and associated range shifts. Realized tree line positions and the potential tree line isotherm are, however, rarely in equilibrium because trees are unable to track rapid temperature variations. Often ignored in tree line research, this dilemma constrains the suitability of tree line trees for understanding alpine vegetation responses to anthropogenic warming. Here, we present combined dendrochronological and wood anatomical assessments of 1,351 seedlings and saplings from three subalpine forest species—larch (Larix decidua Mill.), pine (Pinus cembra L.), and spruce (Picea abies)—collected between ~2,200 and 2,600 m.a.s.l. in the Swiss Alps. We found evidence for temperature-induced, pulse-like seedling germination, rather than a continuous, long-term upward movement. Though the species spread across overlapping elevational ranges, larch was found at the highest elevations, followed by spruce and pine. Surprisingly, we found a varying age structure, with no sign of decreasing age toward higher elevations. Spring and summer temperatures promoted germination pulses, but postgermination survival was likely facilitated by species-specific plant traits. Our study demonstrates the importance of seedling and sapling data from above the tree line to understand prevailing vegetation dynamics at cold temperature extremes and also suggests future tree line advancement in the Swiss Alps.